Are Cbf genes involved in copper tolerance? - Szira, Fruzsina (Acta Biologica Szegediensis, 2008)
A cluster of Cbf (C-repeat binding factor) genes have been shown to have a critical role in cold stress response in many plant species. Extensive cross-talk between abiotic stress-signalling pathways have also been described in recent publications. Since the expression of Cbf genes is known to be influenced by low-temperature, drought or salinity stress, it would be not surprising if their expression would be also influenced by other abiotic stresses such as heavy metal tolerance. In this work the expression pattern of 8 Cbf genes, located on chromosome 5A were investigated in wheat, subjected to different copper stress conditions (hydroponics and soil). Wheat cultivar ‘Chinese Spring’ (moderate copper tolerance) and two 5A chromosome substitution lines, especially ‘Chinese Spring /T. spelta 5A’ (copper sensitive) and ‘Chinese Spring /Cheyenne 5A’ (copper tolerant) showed different expression profiles in the course of copper stress. Cbf3 and Cbf10 were up-regulated by copper stress, especially in the tolerant genotype, however down-regulation of other Cbf genes was also found. These findings suggest that the Cbf genes might have roles in the enhanced copper tolerance.